La despenalización del aborto en Ecuador. Propuesta de reforma al Artículo 447 del Código Penal Ecuatoriano - Jiménez Ochoa, Ivonne Elizabeth (2014)
Within this research entitled “The decriminalization of abortion in Ecuador.Proposed amendment to Article 447 of the Ecuadorian Criminal Code”.The design of today's world and I think , in the mind has always been, the culture has made human sexuality and procreation lose "nature" to biologists , doctors, leaders of the church, moralists and jurists to insist assign , even knowing the falsity of their claims. The reality is that sexual relations between men and women are not aimed exclusively or even primarily, to the reproduction of the species, but favor the desire and pleasure, and every day tends to grow to recognize the trend well and put it publicly. It is so compelling , especially in man, the need to satisfy the sexual need is as necessary as any other organ functions and enjoy it as such, without necessarily want her resulting pregnancy , since biblical times man resorted to withdrawal as a form of contraception. The earliest reference we have of this practice of birth control is in the biblical story of Onan, who according to Jewish tradition , the death of his brother was assumed as the husband of his sister , but could not cohabit with her, " and godliness " , expelled his seed on the ground , which caused his mysterious death . Some people try to rescue this history but to distort its essence and content. The message is intended to give God condemns all forms of sexuality have another destination other than reproduction. But that is not true, or may be construed that way , at least from the current cultural perspective. It is true that God wants to impose a reproduction does not matter in which desire and pleasure. As for birth control is concerned, there is a hurdle so far has been presented as insurmountable. We could not fully understand or agree completely on what is human life and not contraception; it is always played by the Catholic Church, erroneously, as murder. It should, however, point out that the birth control and the right to send in the body itself, has nothing to do with another ideology that is debauchery, that defending the freedom to do what you want with their own body ends paradoxically allowing others to do what they want with that body, whose consequences have nothing to do with responsibility conscious subject of freedom, able to recognize and respond to their own desires and actions. Irresponsible sexual rights without taking adequate contraceptive measures , exercise makes unplanned pregnancies occur or allowed, especially in adolescents and young couples who do not have the maturity necessary psycho-emotive neither the resources and economic independence enable them to cope. But, the problem occurs with considerable frequency in couples living in extreme poverty and have already a number of children they can not keep and, therefore, the arrival of a new stem would , rather than bring joy, to deepen family tragedy. This has made for decades, couples affected by this problem resort to seeking abortion procedures performed clandestinely , often in situations lacking proper hygiene and a good number of cases performed by empirical that lack the preparation or the training necessary to do so, with the consequent production of accidents, complications , sequelae and deaths of young women or fullness of life. The frequency of abortion procedures culminating in permanent sequelae or death of pregnant makes the problem goes beyond the personal, to become a social disadvantage and health that must be addressed with the help of government and society full. In our country the report approved by the Judiciary Committee of the Assembly decriminalized abortion only when the mother 's life is at risk and when the pregnancy results from the rape of a mentally disabled woman . But it is known that only 0.80% is framed in this case lie 99.2% of women raped is in indefección. To Sarahí Maldonado , leader of Women's Movement " abortion ban will only cause these practices are carried out clandestinely in unsafe sites poorly trained staff , which contribute to death rates soar for botched abortions ." The statistics speak for themselves: in citadino revolutionary Ecuador, 18% of maternal deaths are caused by unsafe abortions and 330 deaths occur per 100,000 abortions, well above the 0.1 figure and 0.2% mortality rate in countries where abortion is legal. According to researchers, the statistics show that abortion is decriminalized decreases when the hand of a comprehensive sex education policy. Héctor Pérez Martínez for the analyst, "under contemporary standards of Constitutional and Criminal Law , the Ecuadorian state can only impose sentences of imprisonment when he is unable to conduct combat with other media not negate personal freedom " The crux of the discussion is centered around the idea of life as a fact and as a right. The opposing legal abortion positions based on the premise that the embryo is life , and that idea gives input a moral advantage to opponents of abortion . The question is : where does it begin and end the border of life and if this is micro cell or , on the contrary, responds to a developed state of living cells able to interact with the environment in their own levels of self consciousness a mere relationship ? The legalization of abortion has always been a subject full of religious and political edges, and in recent times,bioethics, because the underlying theme is always the right to life. This depends on whether we consider "human " or " person " to the unborn child, to the new entity, in its early stages, and even in the later stages prior to delivery, we will refer to as "life " or " right to life " who does not have legal capacity and personality, so we can rightly say that the right to abortion is a debate about what makes us people Considering the above I thought pertinent to investigate the following problem: How does the decriminalization of abortion not practiced clandestinely in the city of Loja in 2013